Proteomic responses of carotenoid and retinol administration to Mongolian gerbils. Issue 7 (28th June 2018) - Bohn, Torsten; Planchon, Sébastien; Leclercq, Céline C.; Renaut, Jenny; Mihaly, Johanna; Beke, Gabriella; Rühl, Ralph
Abstract : Determination of protein expression from organs harvested from Gerbils following carotenoid exposure. Abstract : Various health benefits of carotenoids have been described. However, while human observational studies generally suggest positive health effects, supplementation with relatively high doses of individual carotenoids (supplements) have partly produced adverse effects. In the present study, we investigated the effect of several carotenoids on the proteomic response of male Mongolian gerbils (aged 6 weeks). Five groups of gerbils ( n = 6 per group) received either retinol (vitamin A/53 mg per kg bw), all- trans β-carotene (pro-vitamin A/100 mg kg −1 ), the non-pro vitamin A carotenoid lutein (100 mg kg −1 ), the acyclic carotenoid lycopene (100 mg kg −1 ) or vehicle (Cremophor EL), via oral single gavage. Gerbils were 12 h post-prandially sacrificed and blood plasma, liver, and white adipose tissue were collected. For liver and adipose tissue, a 2D-DIGE (difference gel electrophoresis) approach was conducted; for plasma, proteomic analyses were achieved by liquid chromatography-mass spectrometry. Compared to controls (vehicle), various proteins were showing significant abundance variations in plasma (66), liver (29) and adipose tissue (19), especially regarding structure (22), protein metabolism (15) and immune system/inflammation (19) functions, while proteins related to antioxidant effects were generally less abundant, suggesting no in vivo relevance. Surprisingly, a large overlap in protein regulation was found between lycopene and retinol exposure, while other carotenoids, including all- trans β-carotene, did not show this overlap. Mainly retinoid acid receptor co-regulated proteins may mechanistically explain this overlapping regulation. This overlapping regulation may be related to common nuclear hormone receptor mediated signalling, though further studies using synthetic ligands of retinoid receptors targeting protein regulation are needed for confirmation.